Self-heating alkali activated materials: Microstructure and its effect on electrical, thermal and mechanical properties. (13th June 2022) - Fiala, Lukáš; Pommer, Vojtěch; Böhm, Martin; Scheinherrová, Lenka; Černý, Robert
Highlights: Self-heating alkali activated slag mortars (AASMs) with GP are studied. Degree of formation of electrically conductive GP paths in AAM matrix is analyzed. Electrical, thermal and mechanical properties are determined. Links between microstructure and functional properties are assessed. Model formulas for compressive strength – porosity relations are developed. Abstract: Alkali activated materials can be considered as eco-friendly substitutes of Portland cement-based composites which leads to their recent increasing use in the construction industry. In this paper, electrical, thermal, and mechanical properties of alkali activated slag mortars containing graphite powder (GP) in various dosage are analyzed and linked with microstructural characteristics. The use of GP in the amount of 8.75 wt% is found to lead to a good self-heating performance of up to 9.9 W. The electrical conductivity of 4.62·10 −2 S/m, compressive strength of 22.7 MPa, flexural strength of 6.9 MPa, and thermal conductivity of 1.36 W/m·K present a satisfactory mix of properties for most self-heating applications.